EFEKTIVITAS PENERAPAN MODUL AJAR NORMA BERBASIS PROBLEM BASED LEARNING TERHADAP PENINGKATAN KETERAMPILAN BERPIKIR KREATIF SISWA KELAS V SD N TEMPURSARI - Herlina, Herni; Rusmawan (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to analyze the effectiveness of the application of Problem Based Learning (PBL) based norm teaching modules in improving the creative thinking skills of grade V students of SD N Tempursari. The study uses a quantitative approach with a pre-experimental design of the one group pretest posttest. The research subjects amounted to 20 students in class V, consisting of 7 boys and 13 girls. The data collection instrument was in the form of a creative thinking skills questionnaire which included indicators of fluency, flexibility, originality, and elaboration, supported by observation and documentation. The data was analyzed by comparing pretest and posttest scores and calculating N-gain score. The results showed an increase in the average score of creative thinking skills from 2.28 to 3.22 with an N-gain value of 55.24% in the medium category. These findings show that PBL based norm teaching modules are quite effective in improving the creative thinking skills of elementary school students. This teaching module has the potential to be an alternative contextual learning tool that supports the development of 21st century skills, especially in norm learning in elementary schools.